Effectiveness of pharmacological and non-pharmacological methods of pain management in children during venipuncture: a narrative review (Research, Society and Development, 2022)
Recent scientific evidence shows that pain associated with acute painful procedures such as venipuncture is an important source of pediatric pain and may have long-term consequences on the behavior and perception of pain in children. The objective is to verify the efficacy of main pharmacological and non-pharmacological methods of pain management during venipuncture in children. This study is a narrative review of an analytical character with research in PUBMED, SciELO and LILACS databases. As the inclusion criteria, only clinical trials from the year 2016 until the data collection data were selected, selected with the descriptors: “pain”, “venipuncture” and “children”. 31 articles were selected that address different types of pain management during venipuncture, 6 referring to pharmacological methods and 25 to non-pharmacological methods. Among the pharmacological ones, the use of dexmedetomidine, Midazolam, a sucrose solution, topical anesthetic, lidocaine and tetracaine hot adhesive and EMLA cream stands out. As for non-pharmacological ones, the main ones are distraction techniques, including playing video games, reading cards, watching cartoons, listening to music, using toys, interacting with parents, inflating balloons, squeezing the ball, coughing, in addition to more current techniques, such as reality virtual and Buzzy system. Studies have sought to elucidate a greater number of non-pharmacological methods in relation to pharmacological ones, as they are less costly and less traumatic. It is important to highlight distraction techniques, which have a variety of applicable methods, especially those related to hearing and vision.